Native Apps versus Web Apps: which is best for healthcare applications? - Selvarajah, Kirusnapillai; Craven, Michael P.; Massey, Adam; Crowe, John; Vedhara, Kavita; Raine-Fenning, Nick (Springer Verlag, 2013)
Smartphone applications (Apps) provide a new way to deliver healthcare, illustrated by the fact that healthcare Apps are estimated to make up over 30% of new Apps currently being developed; with this number seemingly set to increase as the benefits become more apparent. In this paper, using the development of an In Vitro Fertilisation (IVF) treatment stress study App as the exemplar, the alternatives of Native App and Web App design and implementa-tion are considered across several factors that include: user interface, ease of development, capabilities, performance, cost, and potential problems. Development for iOS and Android platforms and a Web App using JavaScript and HTML5 are discussed.